Pengaruh Tehnology Acceptance Models Terhadap Keputusan Penggunaan OVO Pada Mahasiswa - Sri Rejeki; Hanstaein Mangivera (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this research is to analyze the influence of the benefits, convenience and service features on the decision to use the OVO digital wallet for students. The population used is UIN Raden Mas Said Surakarta students who have used or are currently using the OVO digital wallet. Samples were taken through purposive sampling technique in order to obtain a sample of 100 respondents. The method used is quantitative method. Data analysis used multiple linear regression analysis. The results of the study stated that simultaneously the variables of benefits, convenience and service features influence the decision to use the OVO digital wallet for students. Based on the results of the t test, the benefits and convenience variables have a positive influence on the decision to use. While service features have no influence on usage decisions